Changes in lipid classes of Drosophila melanogaster in response to selection for three stress traits. (August 2019) - Ko, Li; Harshman, Lawrence; Hangartner, Sandra; Hoffmann, Ary; Kachman, Steve; Black, Paul
Graphical abstract: Highlights: Heat increased DAG amounts. Cold increased only PA amounts. Dry changed many lipids. Abstract: Laboratory selection on environmental stress traits is an evolutionary approach that is informative in the context of understanding stress adaptation. Here we characterize changes in a lipidome of Drosophila melanogaster in lines selected for increased heat (elevated heat knockdown refractoriness), cold (decreased time to recover from chill-coma) and desiccation survival. Selection for desiccation resistance resulted in changes in multiple lipid classes used to characterize a lipidome. This included a decrease in triacylglycerols (TAGs) which is relevant to interpretation of storage lipid levels in previous D. melanogaster desiccation survival selection experiments. Chill-coma recovery rate selection was expected to show extensive changes in lipid classes, but only phosphatidic acids exhibited significant change. Selection for increased heat knockdown resistance resulted in a substantial change in the abundance of a class of lipids (diacylglycerols) which could play a role in mediating the heat shock response or result in an increase in neutral lipid mobilization.